A Study on torrefaction of empty fruit bunch and its impact on lignocellulosic structure - Siti Raishan, Mohd Rashid; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (IOP Publishing Ltd, 2020)
Torrefaction is a thermal treatment process used for upgrading lignocellulosic biomass properties into a promising renewable energy, which is performed under inert condition at a temperature range of 200 - 300 C between 15 - 60 minutes residence times. The aim of this study was to investigate the effect of torrefaction treatment on chemical composition and energy properties at different temperature 240, 270, 300 and 330 C with different residence time at 15, 30 and 60 minutes for oil palm biomass (empty fruit bunch). The analysis demonstrated an increase degradation of biomass hence an increase of mass loss was observed due to the combined effect of temperature and treatment duration. Higher heating values was increased by 55% which attributes the energy generations from the torrefied materials. Hemicellulose and cellulose content degraded as temperature and treatment duration increased, while lignin content increased due to the decomposition of hemicellulose and cellulose which accumulated the lignin content in the torrefied biomass. This study proves that torrefied biomass can be used as biofuel as it has higher heating value, and improved the chemical and physical properties of biomass.